Association Between Cytomegalovirus Infection and Bad Obstetric Outcomes in Women from Kirkuk - Hala Mohamed Majeed Hassan; Abdulghani Mohamed Alsamarai; Zainab Khalil Aljumaili; Amina Hamed Alobaidi; Ferah Ghali Alsalihi (Intelektual Pustaka Media Utama, 2014)
The human cytomegalovirus (CMV) is one of the common viral infections worldwide that represent a major causes of congenital infections. To determine the seroprevalence of CMV in women with bad obstetric history and sociodemographic characteristics that may influence the seropositivity, a case control descriptive prospective study was conducted in Kirkuk, Iraq. A 838 women with age range from 14 to 48 were included in the study. Of the total, 547 women were with bad obstetric history(BOH) and 291 women with normal previous pregnancy as control group. All the serum samples collected from the study and control groups were tested for CMV IgM and IgG antibodies by ELISA kits. CMV IgM seroprevalence was higher in women with BOH. CMV IgG seroprevalence was with no significant difference between BOH and control. CMV IgG seroprevalence significantly influenced by age, education, smoking, and family size. However, CMV IgM seroprevalence significantly associated with pregnancy, residence, and animal exposure. Odd ratio confirmed the association between CMV IgG and age, crowding index, residence, smoking, and number of abortion in women with BOH. In addition, current CMV infection significantly associated with residence in women with BOH.